2014
DOI: 10.1016/j.annepidem.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and age at menarche: an examination of multiple indicators in an ethnically diverse cohort

Abstract: Purpose Ethnic disparities exist in US girls' ages at menarche. Overweight and low socioeconomic status (SES) may contribute to these disparities but past research has been equivocal. We sought to determine which SES indicators were associated uniquely with menarche, for which ethnic groups, and whether associations operated through overweight. Methods Using National Longitudinal Study of Youth data, we examined associations between SES indicators and age at menarche. Participants were 4851 girls and their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 38 publications
(41 reference statements)
6
61
1
Order By: Relevance
“…8 Prior studies, mostly from the USA, have described socioeconomic and ethnic/racial patterning of the onset of puberty. [9][10][11][12][13][14] Given the different historical and geographical patterns of migration to the UK and USA we might not necessarily expect to see ethnic differences in early puberty in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…8 Prior studies, mostly from the USA, have described socioeconomic and ethnic/racial patterning of the onset of puberty. [9][10][11][12][13][14] Given the different historical and geographical patterns of migration to the UK and USA we might not necessarily expect to see ethnic differences in early puberty in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examined SEP and age at menarche are inconsistent, with some finding lower SEP directly related to earlier menarche (1720) and others the inverse (2123). This inconsistency may be at least in part due to the changing relationship of SEP with body size over time (24, 25) and the association of obesity with race and ethnicity (26).…”
mentioning
confidence: 99%
“…Also, Black and Hispanic girls experienced menarche earlier than whites. SES indicators were associated uniquely with earlier menarche and included mother's unmarried status and lower family income (Deardorff et al 2014). However, the other polish studies (female university students) from Szczecin showed that there were no significant differences in the number of the early, average and late maturing students between the socioeconomic groups (Olszewska et al 2015).…”
Section: Discussionmentioning
confidence: 99%